THE INTEGRATION OF FORMATIVE AND SUMMATIVE ASSESSMENT IN ENGLISH LANGUAGE TEACHING - Ramazonova Feruza Akbarovna,; Tashmetov Azizbek Ravshan Oʻgʻli, (TADQIQOTLAR, 2026)
Article  explores  the  integration  of  formative  and  summative  assessment  in English language teaching, emphasizing the importance of both assessment types in enhancing student learning outcomes. Formative assessment, which occurs during the learning process, provides ongoing feedback to students and teachers, allowing for adjustments in instruction and learning strategies. Summative assessment, conducted at  the  end  of  an  instructional  period,  evaluates  student  learning  against  specific benchmarks  or  standards.  The  article  discusses  various  strategies  for  effectively combining  these  assessments,  such  as  using  formative  assessments  to  inform summative evaluations and ensuring that both types of assessments align with learning objectives. By integrating formative and summative assessments, educators can create a  more  holistic  approach  to  evaluating  student  progress  and  fostering  language development.